IMPLEMENTATION OF EMPLOYEE GATHERING PROGRAMME IN IMPROVING THE QUALITY OF COACHING ACTIVITIES IN CORRECTIONAL INSTITUTIONS CLASS IIB TANJUNG PATI - Kahfi, Muhibbul; Warih, Wido Cepaka (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This research focuses on the implementation of the Employee Gathering program in improving the quality of coaching activities at Class IIB Tanjung Pati Correctional Institution. This research aims to analyze the program's implementation and identify the obstacles faced in its implementation. The research method used is a qualitative approach, with interviews, observation, and documentation as data collection techniques. This approach was chosen to understand social interactions and phenomena that occur in prison in depth. The results showed that the Employee Gathering program positively impacted the officers' motivation and morale, as well as strengthened the relationship between officers. In conclusion, the Employee Gathering program has contributed to improving the quality of coaching but requires improvement in the aspects of planning, budget management, and more equitable participation to achieve optimal results. Keywords: Employee Gathering; Quality; Coaching; Correctional Institution